Pokok-Pokok Hukum Kewarisan (Analisis Kehujahan Hadis Dengan Pendekatan Kritik Sanad) - Zulfahmi Zulfami (Universitas Islam Negeri Alauddin, 2013)
Since property issues became a source of greed and familial rift, Islam provided regulations regarding the distribution of inheritance for the heirs. The regulations have been described by Allah and the Prophet in the Koran and Hadith. Those regulations should become a guide for Muslims when they execute the distribution of inheritance to those who deserve it in order to avoid unfair distribution of inheritance it self. The study of the four main points of the hadith about inheritance law found that one of them is shahih. The hadith is about the status of the Prophet who did not inherit. Two of them are shahih li ghayrih. Both are hadith about the rights of women in inheritance and the prohibition for people of different religions to inherit each other. The rest of hadith is dha’if. The hadith is about the rights of wife and daughters to inherit. This study is expected to become a reference for managing the inheritance in Islamic society. That is important to avoid misunderstanding about the regulations of inheritance stated in the Koran and hadith. This study also significant to reduce the potential for family rift caused by the unfair distribution of inheritance.